ELECTROKINETIC PROPERTIES, IN VITRO DISSOLUTION, AND PROSPECTIVE HEMOAND BIOCOMPATIBILITY OF TITANIUM OXIDE AND OXYNITRIDE FILMS FOR CARDIOVASCULAR STENTS - I. A. Khlusov; V. F. Pichugin; A. A. Pustovalova; M. E. Konischev; A. N. Dzyuman; M. Epple; M. Ulbricht; E. Cicinskas; V. S. Gulaya; V. V. Vikhareva (Бюллетень сибирской медицины, 2015)
A state of titanium oxide and oxynitride coatings on L316 steel has been studied before and after their contact with model biological fluids. Electrokinetic investigation in 1 mmol potassium chloride showed significant (more than 10 times) fall of magnitude of electrostatic potential of thin (200–300 nm) titanium films at pH changing in the range of 5–9 units during 2 h. Nevertheless, zeta-potential of all samples had negative charge under pH > 6.5. Long-term (5 weeks) contact of samples with simulated body fluid (SBF) promoted steel corrosion and titanium oxide and oxynitride films dissolution. On the other hand, sodium and chloride ions precipitation and sodium chloride crystals formation occurred on the samples. Of positive fact is an absence of calcification of tested artificial surfaces in conditions of long-term being in SBF solution. It is supposed decreasing hazard of fast thrombosis and loss of materials functional properties. According to in vitro experiment conducted, prospective biocompatibility of materials tested before and after their contact with SBF lines up following manner: Ti–O–N (1/3) > Ti–O–N (1/1), TiO2 > Steel. It may be explained by: 1) the corrosion-preventive properties of thin titanium oxide and oxynitride films;2) a store of surface negative charge for Ti–O–N (1/3) film; 3) minor augmentation of mass and thickness of titanium films connected with speed of mineralization processes on the interface of solution/solid body. At the same time, initial (before SBF contact) differences of samples wettability became equal. Modifying effect of model biological fluids on physicochemical characteristics of materials tested (roughness enhancement, a reduction or reversion of surface negative potential, sharp augmentation of surface hydrofilicity) should took into account under titanium oxide and oxynitride films formation and a forecast of their optimal biological properties as the materials for cardiovascular stents.